Ecotourism Attractions, Level of Satisfaction and Management of Air Terjun Kembar in Kampung Anyar Village, Banyuwangi - Alfian, Alfian; Sulistyadi, Febi Wahyu; Samuel, Pratama Diffi; Naitio, Emanuel (Graduate School, Universitas Brawijaya, 2016)
Air Terjun Kembar (Twin Waterfall) in Kampung Anyar, Banyuwangi is an alternative tourist travel destinations around the Ijen crater. This study aims to determine the history, attractions, eco-tourism potential, the level of customer satisfaction and further management for the area. The method is carried out by semi-structured interviews, questionnaires based on the satisfaction level of Sapta Pesona (standard value) and SWOT Analysis to the management. These results indicate that previously Kembar Waterfall Kampung Anyar was used for water resources. Then, in 2014 began to be managed by the group of people in Kampung Anyar. SWOT analysis shows that the management is good. In some aspect however it needs to be improved. Keywords: Ecotourism, Kampung Anyar, Sapta Pesona, SWOT.